Personal history - Graham, Katharine, 1917-2001. (New York : Vintage, 1998)
The author describes her privileged but lonely childhood, her tragic marriage to the charismatic Phil Graham, her struggles as the head of the Washington Post, and the colorful politicians and celebrities she has known.
Includes index.
Pulitzer Prize for Autobiography, 1998.
Keywords: Graham, Katharine, -- 1917-2001.; Washington post (Washington, D.C. : 1974) -- History; Newspaper publishing -- Washington (D.C.) -- History -- 20th century; Publishers and publishing -- United States -- Biography; Autobiographies